Village Fund Reform: A Proposal for More Equitable Allocation Formula - Paellorisky, M. Olgiano; Solikin, Akhmad (Jurnal Bina Praja, 2019)
The allocation of Village Fund as stipulated in the Minister of Finance Regulation number 49/PMK.07/2016, i.e. basic allocation (alokasi dasar) 90% and formula allocation (alokasi formula) 10%, could be considered as unequal because of poor attention to the indicators of poverty and development of each village. Basic allocation relates to the same amount of allocation per village, while formula allocation refers to an allocation based on the number of populations in poverty, size of area, and infrastructure price index. This article aims to investigate the ideal allocation proportion of village funds. Methods used in this study were a correlation and the analytical hierarchy process. The results show a stronger correlation between village fund and poverty and development indicators if more money is allocated in the formula allocation. However, an inequality of allocation ratio and larger fund are needed to achieve the program’s targets. Based on the weighted value of the expert group perception, the proposed formula for the ratio of basic allocation (alokasi dasar) and formula allocation (alokasi formula) is 10:90. With this formula, it is expected that poverty and development can be more quickly resolved. So, the purpose of the Village Fund as mandated by Law Number 6/2014 could be achieved.